The Anomalously Old Bush Stream Rock Avalanche and Its Implications for Landslide Inventories in Dynamic Landscapes - McColl, Samuel T. (Frontiers in Earth Science, 2020)
Previous dating of rock slope failures in most glaciated mountain chains has revealed almost exclusively young, mostly Holocene ages. In this study, a rock avalanche in the glaciated Rangitata Basin in Canterbury, New Zealand is mapped, described, and dated, revealing a pre-Holocene age of failure. The geomorphology and characteristics of the rock avalanche, named here as the Bush Stream Rock Avalanche, were assessed from field mapping and photogrammetric analyses. To assess the age of the rock avalanche, in situ cosmogenic 10Be exposure dating was applied to boulders on the deposit. The geomorphological mapping shows that the morphology of the head scarp and deposit of the rock avalanche are distinct from the surrounding landscape, much of which appears to be glacial in origin. The rock avalanche traveled about 4 km, with a volume of 50–100 M m3, and appears to have temporarily blocked Bush Stream. The dated boulders suggest an age of >16 ka (and likely >20 ka), making it the oldest reported alpine rock avalanche in New Zealand, and one of the oldest last-glaciation rock avalanches to be reported worldwide. Deep depressions, possibly kettle holes, in the deposit are indicative of runout over a glacier (or associated dead ice), but any glacier present at the time must have been small and probably decaying. The excellent preservation was likely favored by a small catchment located on the dry lee side of the Two Thumb Range which dampened glacial and fluvial activity. The study confirms that rock avalanches were being produced in the Southern Alps early in the last glaciation or early period of deglaciation, but that evidence for them likely exists only in the rare environments that have conditions favorable for preservation. Preservation potential in most of the Southern Alps is low, with older deposits readily buried or eroded by New Zealand’s high rates of erosion, aggradation, and dynamic processes. Unless methods can be developed to identify missing older events, we are hampered in our ability to understand the frequency, and therefore causes, of large slope failures in the Southern Alps and in other highly dynamic alpine landscapes.